Evaluation of arsenic, cobalt, nickel, lead, mercury, and titanium in goat blood and hair reared in Sicily and insights into blood biomarkers - Fazio, Francesco; Nava, Vincenzo; Bruno, Fabio; Licata, Patrizia; Giannetto, Claudia; Piccione, Giuseppe; Cannuli, Antonio; De Caro, Salvatore; Aragona, Francesca (Frontiers in Veterinary Science, 2026)
IntroductionExposure to harmful trace elements can lead to their accumulation in various biological substrates, resulting in the development of acute and chronic diseases in humans and animals. The knowledge of bioaccumulation of trace elements in different biological substrates could provide important information on exposure to trace elements through the use of sentinel animals. The aim of this research was to study the potential bioaccumulation of various trace elements (Arsenic-As, Cobalt-Co, Nickel-Ni, Lead-Pb, Mercury-Hg and Titanium-Ti) in goat blood and hair and their relationship with haematological biomarkers.MethodsHair was collected from 25 non-pregnant and non-lactating clinical healthy goats aged between 2 and 3 years reared in Sicily, to determine trace elements concentration by means of inductively coupled plasma mass spectrometer (ICP-MS). Blood in duplicate was collected at the same time to determine trace element concentration and haematological profile. A paired t-test and multiple regression analysis was performed to evaluate the relationship among As, Co, Ni, Pb, Hg and Ti and blood and hair, together with their relationship with haematological parameters, respectively.Results and discussionStatistical analysis showed a significant higher concentration of As (p < 0.0001) and Pb (p < 0.0001) in blood compared to hair and higher concentration of Co (p < 0.0001), Ni (p < 0.0001), Hg (p < 0.0001), and Ti (p < 0.0001) in hair compared to blood. Blood As and Ti showed a positive correlation with HGB (r = 0.48; p < 0.01; r = 0.52; p < 0.01). Blood Pb and Ti showed a positive correlation with HCT (r = 0.52; p < 0.01; r = 0.52; p < 0.01) and a negative correlation was observed for blood Co and WBC (r = −0.45; p < 0.01). The analysis of the results clearly indicates a strong correlation between the bioaccumulation of certain trace elements and some haematological parameters. These results should be examined thoroughly in goats to understand the significance of haematological factors in productive and reproductive activities.